Calculating of Some Exhaust Emission Compounds of Diesel Engine Generators in Sulaimani City Using Energy-Based Approaches. - Mohammed, Karzan Q.; Majid, Salih N.; Aziz, Hunar B.; Hamza, Aven R.; Ismael, Karzan S. (Sulaimani Journal for Pure and Applied Sciences, 2020)
In Kurdistan region of Iraq similar to developing countries, diesel engine generators (DEGs) have established themselves as reliable, durable and complementary suppliers to the main national grid of electric power for domestic, industrial, agriculture and commercial sectors. By domestic purpose, the generators are usually placed close to the residents in all the districts of the cities. However, diesel emissions contain numerous compounds that are evidenced to be a threat to humans and have the potential to cause adverse health effects. Furthermore, diesel emissions are particularly a significant hazard to the environment as well as they are significant contributors to global greenhouse gas (GHG) emissions. In view of the previous reasons, there was an urgent need to evaluate and quantify the exhaust emission of diesel generators by applying energy-based approaches. Consequently, this study aimed to calculate the exhaust emission compounds of CO2, CO, NOx, SO2, and HC by applying energy-based approaches based on fuel consumption for the past three years of 2013, 2014 and 2015 in Sulaimani city, Kurdistan Region, IRAQ because no previous studies have yet been conducted for this issue. Results indicated that the calculated amounts of the emitted gases had the following increasing trends; CO2 > NOx > SO2 > CO > HC. The percent of domestic source out of the total emission for all investigated gases was in the range of 90.95 to 98.13%. The amount of annual emission for all the investigate gases have increased obviously through the year’s progression of 2013 to 2015 due to the increasing of DEGs numbers and more electric power consumption.
Keywords: Diesel powered-generator; Exhaust emission; Commercial and domestic sources; Energy-based approach; Sulaimani city